PEMILIHAN TOPIK TERKINI PADA MEDIA ONLINE TIMLO.NET DALAM MEMBENTUK MOTIVASI DAN DAYA TARIK PENGUNJUNG DI KALANGAN MAHASISWA UNISRI - Siswanto & Bedjo Sukarno, Daryono (Transformasi, 2014)
This research is a descriptive qualitative study describing the current topic selection on online media Timlo.net in the form of motivation and visitor attraction among the students of slamet riyadi university. By using technique validity data namely triangulation, the results of this research is the current topic of the selection Timlo.net refers to news value, development of the issues and local content. Determination of current topics based on news value in accordance with the needs of the visitor desiring information news in accordance with the information they need. Current topics that raise local content is also in accordance with the needs of the visitor desiring information local information that is rarely discussed in other media. A theme that is in an adoptive have to actual and factual. Key words : the current topic, online media , visitor’s motivation , news value.